Friction stir superplasticity for unitized structures - Ma, Zongyi; Mishra, Rajiv S. (Butterworth-Heinemann, 2014)
Friction stir superplasticity has reached a point where designers have opportunities to expand the extent of unitized structures, which are structures in which the traditional primary part and any supporting structures are fabricated as a single unit. With advanced optimization and material considerations, this class of structures can be lighter weight and more efficient, making them less costly, as well as mechanically less complex, reducing areas of possible failure. This book discusses how friction stir processing allows selective microstructural refinement without thickness change and demonstrates how higher thickness sheets and plates can be superplastically formed. It includes examples for aluminum, magnesium and titanium alloys and covers the production of low-cost unitized structures by selectively processing cast sheets/plates. --
Includes bibliographical references. - Online resource; title from PDF title page (ScienceDirect, viewed June 5, 2014)
Keywords: Superplasticity; Friction stir welding; Welding; Superplasticité; Soudage par friction-malaxage; Soudage; welding; TECHNOLOGY & ENGINEERING; Engineering (General); TECHNOLOGY & ENGINEERING; Reference